Little Historian Model for Local History Learning (History Department, Semarang State University and Historian Society of Indonesia, 2022)
Based on a preliminary study of learning activities and learning resources used in MAN 1 Surakarta, it is known that teachers are less varied in using innovative learning models in history learning. This study aims to: (1) analyze the pre-conditions of developing learning models in students' history learning activities; (2) analyze the process of developing a little historian model with the material content of the History of the Surakarta Kasunanan Palace; and (3) analyze the feasibility level of the learning model that has been developed. The research method used is Research and Development (RD) with the following stages: a preliminary study of the conditions of historical learning and a study of the development of learning models. This research focuses on developing a little historian model of learning. The results showed that teachers only used worksheets and textbooks in learning. While the learning method used is the method of assignment and discussion. Based on the results of the validation process for the product developed in the form of a learning model packaged in the form of a module in the first stage, it showed a total average percentage of 91.84%. The second stage of the validation process showed an increase of 3.3% to 95.14%. The validation results show that the little historian learning model developed is feasible to use without revision based on the validation results by learning model experts on historical material during the Islamic civilization in Indonesia. Berdasarkan studi pendahuluan terhadap kegiatan pembelajaran dan sumber belajar yang digunakan di MAN 1 Surakarta diketahui bahwa guru kurang bervariasi dalam menggunakan model pembelajaran inovatif di dalam pembelajaran sejarah. Penelitian ini bertujuan: (1) menganalisis pra kondisi pengembangan model pembelajaran pada kegiatan belajar sejarah siswa; (2) menganalisis proses pengembangan model sejarawan kecil dengan muatan materi Sejarah Keraton Kasunanan Surakarta; dan (3) menganalisis tingkat kelayakan model pembelajaran yang telah dikembangkan. Metode penelitian yang dipakai adalah Research and Development (RD) dengan tahapan berikut: studi pendahuluan tentang kondisi pembelajaran sejarah dan studi pengembangan model pembelajaran. Fokus penelitian ini yaitu untuk mengembangkan model pembelajaran sejarawan kecil berbasis sejarah lokal. Hasil penelitian menunjukkan bahwa guru hanya menggunakan LKS dan buku paket dalam pembelajaran. Sedangkan metode pembelajaran yang digunakan adalah metode penugasan dan diskusi. Berdasarkan hasil dari proses validasi terhadap produk yang dikembangkan berupa model pembelajaran yang dikemas dalam bentuk modul pada tahap pertama menunjukkan presentase rata-rata total sebesar 91,84%. Proses validasi tahap kedua menunjukkan peningkatan presentase sebesar 3,3% menjadi 95,14%. Berdasarkan hasil validasi tersebut menunjukkan bahwa model pembelajaran sejarawan kecil yang dikembangkan layak untuk digunakan tanpa revisi berdasarkan hasil validasi oleh ahli model pembelajaran di kelas X pada materi sejarah zaman kerajaan Islam di Indonesia. Cite this article: Soeharso, R. Sodiq, I. Wardayanti, R. (2022). Utilization Little Historian Model for Local History Learning. Paramita: Historical Studies Journal, 32(2), 306-314. http://dx.doi.org/10.15294/paramita.v32i2.29962